In Silico Investigation of EDTA-Functionalized ZSM-5 as a Rifampicin Drug Delivery System Against Tuberculosis-Related Targets - Indra Lasmana Tarigan; Nadia Rahmasari; Chairanisa Intan Kartika; Jonathan Sabar Simorangkir; Ailsa Putri Dyanti; Muhammad Irfan Nur Widad (Jurnal Kartika Kimia, 2026)
Tuberculosis (TB) is a major infectious disease caused by Mycobacterium tuberculosis. Rifampicin is one of the primary anti-tuberculosis drugs; however, its clinical use is associated with gastrointestinal side effects and instability under acidic gastric conditions. Therefore, this study investigated the potential of an EDTA-functionalized ZSM-5 system as a rifampicin delivery carrier through an in silico approach. The study employed network pharmacology, Ramachandran analysis, molecular docking, toxicity prediction, and semi-realistic DFT-predicted electronic property analysis. Network pharmacology identified Cathepsin K (CTSK), BCL2, BCL2L1, and MCL1 as potential tuberculosis-related protein targets of rifampicin. Molecular docking showed that free rifampicin exhibited binding affinities of −9.1, −6.4, −9.7, −6.9, and −7.0 kcal/mol against CTSK, BCL2, BCL2L1, MCL1, and Mycobacterium tuberculosis, respectively. Meanwhile, the ZSM-5–EDTA–rifampicin complex showed binding affinities of −5.9, −5.6, −6.1, −6.0, and −7.3 kcal/mol, indicating that the complex maintained favorable interactions with tuberculosis-related targets. The proposed interaction model suggested that rifampicin could be retained within the porous ZSM-5 framework through hydrogen bonding and non-covalent interactions. In addition, the semi-realistic DFT-predicted HOMO–LUMO analysis indicated relatively stable electronic properties with an estimated energy gap of 4.34 eV. Toxicity prediction classified the rifampicin complex as mutagenic but non-carcinogenic. Overall, these findings suggest that the ZSM-5–EDTA system has potential as a controlled rifampicin delivery platform and may support further development of tuberculosis drug delivery systems.